Analisis Pendapatan Peternak dan Efisiensi Pemasaran Ayam Ras Pedaging (Broiler) (Studi Kasus: UD. Kubu Saren yang Bekerjasama dengan Peternak) - DEWI, NI MADE CAHYANI SUKMA; SUAMBA, I KETUT; WIDHIANTHINI, WIDHIANTHINI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.11, No.1, Juli 2022DO - 10.24843/JAA.2022.v11.i01.p09, 2022)
Analysis of Farmer Income and Marketing Efficiency of Broiler Chickens  (Case Study of UD. Kubu Saren and Its Farmer Partners).  Broiler chicken farming in Indonesia is growing every year and helps meet the needs of animal protein. Broiler chickens have a fairly short maintenance period. As such, broiler chicken farming is a potential business. One of the factors that determine the success of broiler chicken farming is marketing. The study aims to (1) determine the income of broiler farmers in partnership with UD. Kubu Saren, (2) to determine the level of marketing efficiency of broiler chicken of UD. Kubu Saren which is seen  from the marketing margins in each marketing channel, (3) knowing the problems  faced by farmers during the pandemic. This research was conducted at UD. Kubu Saren, Rianggede Village, Penebel District, Tabanan Regency, Bali Province from September to October 2020. The data collected were quantitative and qualitative data with primary and secondary data sources. The collected data were analyzed using descriptive quantitative method. This study uses non probability sampling techniques, namely saturated sample method or census of 25 respondents who are partners of UD. Kubu Saren. The variables measured in this study include farmers income, marketing efficiency and the problems faced by farmers. The results show that the farmer’s average income is IDR 1.236,48/chicken/period with the level of marketing efficiency in the range of 0-33%, namely 4.547% Covid-19 caused several problems for breeders, namely internal problems related with the rising price of livestock production facilities (40% of respondents) and external problems related with lack of government attention (53% of respondents). Farmers should increase the number of Day Old Chicks to increase income.